Two-Dimensional Metallic NiSe2 Nanoclusters–Based Low-Cost, Flexible, Amperometric Sensor for Detection of Neurological Drug Carbamazepine in Human Sweat Samples - Veeralingam, Sushmitha; Badhulika, Sushmee (Frontiers in Chemistry, 2020)
Here we report a low cost, flexible amperometric sensing platform for highly selective and sensitive detection of carbamazepine (CBZ) in human sweat samples. Detailed morphological characterization of the 2-Dimensional (2D) Transition metal Dichalcogenide (TMDC) NiSe2, synthesized using one-step hydrothermal method, confirms the formation of dense NiSe2 nanoclusters in the range of 500 nm - 650 nm while XRD and XPS studies reveal a stable and pure cubic crystalline phase of NiSe2. The sensor device is fabricated by uniformly depositing an optimized weight percentage of as-synthesized NiSe2 onto flexible and biocompatible Polyimide (PI) substrate using spin coating and metal contacts are established using thermal evaporation technique. The sensor exhibits a remarkable sensitivity of 65.65 µA/nM over a wide linear range of 50 nM - 10 µM CBZ concentrations and a low limit of detection (LOD) of 18.2 nM. The sensing mechanism and excellent response of NiSe2 towards CBZ can be attributed to the highly conductive metallic NiSe2, large electro-active surface area of its nanoclusters and highly interactive Ni2+/Ni3+ oxidation states. Furthermore, the presence of 10-folds excess of capable interferents such as lactic acid, glucose, uric acid and ascorbic acid do not affect the accurate determination of CBZ thus, demonstrating excellent selectivity. The real-time detection of CBZ is evaluated in human sweat samples employing standard addition method which yields reliable results. Furthermore, the sensor shows excellent robustness when subject to bending cycles and fast response time of 2 s. The strategy outlined here is useful in developing sensing platforms at low potential without the use of enzymes or redox binders for applications in healthcare.